2002
DOI: 10.2337/diacare.25.6.1015
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Diabetes Metabolic Control and Drug Adherence in an Indigent Population

Abstract: Adherence to medication regimens for type 2 diabetes is strongly associated with metabolic control in an indigent population; African-Americans have lower adherence and worse metabolic control. Greater efforts are clearly needed to facilitate diabetes self-management behaviors of low-income populations and foster culturally sensitive and appropriate care for minority groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
232
5
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(277 citation statements)
references
References 51 publications
22
232
5
8
Order By: Relevance
“…This was similar to racial differences in insulin self-management in an indigent population reported by Schectman et al (25). Additional outreach may be needed to African-American veterans to determine how the system can better serve them.…”
Section: Research Design Andsupporting
confidence: 60%
“…This was similar to racial differences in insulin self-management in an indigent population reported by Schectman et al (25). Additional outreach may be needed to African-American veterans to determine how the system can better serve them.…”
Section: Research Design Andsupporting
confidence: 60%
“…Our estimate of a persistent racial gap in A1C is consistent with the findings of Schectman et al (13), who found evidence of a racial gap in A1C after controlling for medication adherence to oral medications. Our findings differ from those of Pladevall et al (12), who found no evidence of racial differences in glycemic control after controlling for adherence to metformin.…”
Section: Baseline Differences By Racesupporting
confidence: 82%
“…We used nonparametric tests (Kolmogorov-Smirnov) (19) to assess racial differences in the number of physician visits and the number of A1C tests. Median months of follow-up were similar for black (median 51 [minimum 13, maximum 108) and white patients (52 [13,108]). …”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Prior work in medication adherence shows that adherence rates may be lower for certain ethnic minorities. [26][27][28][29] Differences in health beliefs and use of alternative therapies may explain some differences found in adherence rates for special populations. [30][31][32] Replicating this study in special populations could yield novel and clinically useful results.…”
Section: Discussion/conclusionmentioning
confidence: 99%